2007
DOI: 10.1088/1126-6708/2007/05/032
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing scalar invariant spacetimes in supergravity

Abstract: Abstract. We show that the higher-dimensional vanishing scalar invariant (VSI) spacetimes with fluxes and dilaton are solutions of type IIB supergravity, and we argue that they are exact solutions in string theory. We also discuss the supersymmetry properties of VSI spacetimes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 34 publications
0
67
0
Order By: Relevance
“…In [22] it was shown that the higher-dimensional VSI spacetimes with fluxes and dilaton are solutions of type IIB supergravity. Exact VSI solutions of IIB supergravity with NS-NS and RR fluxes and dilaton have been constructed.…”
Section: Vanishing Curvature Invariants (Vsi)mentioning
confidence: 99%
See 1 more Smart Citation
“…In [22] it was shown that the higher-dimensional VSI spacetimes with fluxes and dilaton are solutions of type IIB supergravity. Exact VSI solutions of IIB supergravity with NS-NS and RR fluxes and dilaton have been constructed.…”
Section: Vanishing Curvature Invariants (Vsi)mentioning
confidence: 99%
“…Therefore, a necessary (but not sufficient) condition for a particular supergravity solution to preserve some supersymmetry is that the spacetime possess such a Killing vector. Therefore the supersymmetry properties of VSI type IIB supergravity solutions with a CCNV were studied [22]. Supersymmetry was also studied in the CSI-CCNV subclass of supergravity spacetimes [25].…”
Section: Vanishing Curvature Invariants (Vsi)mentioning
confidence: 99%
“…It has of course long been known that pp-waves with flat transverse space provide such backgrounds since all the scalar invariants vanish identically -recently the class of exact sugra solutions with vanishing scalar invariants was investigated in [1]-but they are exceptional.…”
mentioning
confidence: 99%
“…Both the higher-dimensional VSI and CSI spacetimes are known to to admit solutions to supergravity theories [17,18]. Furthermore, the PP-wave spacetimes have been proven to be solutions to the vacuum equations of all gravitational theories with a Lagrangian constructed from SPIs [19].…”
Section: Introductionmentioning
confidence: 99%